Nigrospora guangdongensis sp. nov. from the needle of Cunninghamia lanceolata in China - Tian, Long-Yan; Zhang, Yan-Feng; Lian, Tao; Qin, Chang-Sheng; Xu, Jin-Zhu (Phytotaxa, 2020)
Nigrospora is a genus occurring on various substrates as pathogens, saprophytes or endophytes. In this study, Nigrospora strains were isolated from the needles of Cunninghamia lanceolata in Guangdong province of China. According to the morphological and phylogenetic evidence, it can be recognized as a new species. Hereby, Nigrospora guangdongensis sp. nov. is introduced and it can be distinguished from its phylogenetically close species, by having sparse, discrete, and solitary conidiophores with sporadic conidia.